Nilai Relatif Kebudayaan Dan Nilai Absolut Agama Islam Dalam Pendidikan - Rosmiati, Rosmiati; Jamilus, Jamilus (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Cultural relativism is a view that culture has its own worldview. It can also be defined as a person's perspective (a tribe, religion, nation) in seeing other people's habits (culture) that are firmly entrenched in life and practiced in everyday life. Value is a quality provision that is meaningful for individual human life, society, nation and state. The presence of values ​​in human life can generate actions and reactions, so that humans will accept or reject their presence. As a consequence, values ​​will become life goals that want to be realized in the reality of everyday life. For example, the values ​​of justice and honesty are values ​​that have always been a human concern to be realized in reality. Implementation of education one way is through school education. In the whole process of education in schools teaching and learning activities are the main activities. Learning cannot be separated from teaching, students learn because educators teach and vice versa. One effort to optimize learning outcomes is to improve teaching, which in this case is mostly determined by educators